Evaluation of 4D CT acquisition methods designed to reduce artifacts. (8th March 2015) - Castillo, Sarah J.; Castillo, Richard; Castillo, Edward; Pan, Tinsu; Ibbott, Geoffrey; Balter, Peter; Hobbs, Brian; Guerrero, Thomas
Abstract : Four‐dimensional computed tomography (4D CT) is used to account for respiratory motion in radiation treatment planning, but artifacts resulting from the acquisition and postprocessing limit its accuracy. We investigated the efficacy of three experimental 4D CT acquisition methods to reduce artifacts in a prospective institutional review board approved study. Eighteen thoracic patients scheduled to undergo radiation therapy received standard clinical 4D CT scans followed by each of the alternative 4D CT acquisitions: 1) data oversampling, 2) beam gating with breathing irregularities, and 3) rescanning the clinical acquisition acquired during irregular breathing. Relative values of a validated correlation‐based artifact metric (CM) determined the best acquisition method per patient. Each 4D CT was processed by an extended phase sorting approach that optimizes the quantitative artifact metric (CM sorting). The clinical acquisitions were also postprocessed by phase sorting for artifact comparison of our current clinical implementation with the experimental methods. The oversampling acquisition achieved the lowest artifact presence among all acquisitions, achieving a 27% reduction from the current clinical 4D CT implementation ( 95 %   confidence interval = 34 − 20 ). The rescan method presented a significantly higher artifact presence from the clinical acquisition (37%; p < 0.002 ), the gating acquisition (26%; p < 0.005 ), and the oversampling acquisition (31%; p < 0.001 ), while the data lacked evidence of a significant difference between the clinical, gating, and oversampling methods. The oversampling acquisition reduced artifact presence from the current clinical 4D CT implementation to the largest degree and provided the simplest and most reproducible implementation. The rescan acquisition increased artifact presence significantly, compared to all acquisitions, and suffered from combination of data from independent scans over which large internal anatomic shifts occurred. PACS numbers: 87.57.C‐, 87.57.cp, 87.57.Q‐, 87.55.Gh